Rancang Bangun Alat Pendeteksi Zat Berbahaya Pada Makanan Berbasis Internet of Things (IoT) - Edy, Rizma Ruqayyah; Nurdin, Ali; Suroso, Suroso (Forum Kerjasama Pendidikan Tinggi, 2024)
As technology advances public awareness of food safety is increasing. Food safety is a crucial issue that requires special attention, especially regarding the use of hazardous substances in food. The misuse of these hazardous substances has led to many people suffering from food poisoning, which can cause serious health problems such as shortness of breath, diarrhea, allergies, kidney irritation, and even cancer. Despite many efforts to address this issue, the results have not been satisfactory. Therefore, the aim of this research is to use the Internet of Things (IoT) to design and build a device that can identify hazardous substances in food. This device detects potentially harmful substances using a TCS3200 sensor, which works by detecting the RGB (Red, Green, Blue) frequency values of food samples suspected of containing hazardous substances. The detection data is then sent to a server and the MIT App Inventor application via the internet, allowing real-time monitoring through Android devices. Testing results show that this detection device achieves an accuracy rate of 97.91% with an error margin of 2.09% and can display data in real-time on the Android application. The correlation between RGB values and the concentration of hazardous substances indicates that the higher the content of hazardous substances, the lower the detected RGB values, while higher RGB values indicate a darker color due to the presence of hazardous substances. This device is expected to help the public ensure food safety and raise awareness of the dangers of using hazardous substances. With this device, the public is expected to be more vigilant and protected from potential health risks due to consuming food containing hazardous substances. Additionally, this technology has the potential to be further developed to detect various other types of hazardous contaminants in the future.